Model Penyelewengan Pajak Menggunakan Faktur Pajak Fiktif - YAMIN, LUIYANTO; PUTrANTI, TITI MUswATI (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2011)
Under the Value Added Tax (VAT) system, the validity of the collection is indicated by the issue of tax-invoice. Without tax-invoice, the taxable firm can be assumed not doing their obligation to collect VAT, whereas the buyer may be regarded as not paying VAT. The invoice is very important for the VAT mechanism. Zero-rate on export facilitates the exporters to claim refund on some input taxes. However, the ease and simplicity of VAT refund has been abused by taxable firms and non taxable firms with the aid of tax officers. This study is aimed to analyze the causal factors of the case of tax-invoice fraud. The study is based on the analysis of interview results with the key informants. There are at least 22 models of tax-invoice fraud occurred on exports. Four main causes for the tax-invoice fraud: (1) the complexity in credit mechanism, (2) poor tax administration, (3) lack of tax audit, and (4) the culture of society. To anticipate the cases of tax-invoice fraud, the government has issued several regulations and circulated letters, including carried out risk analysis in connection with the auditing on VAT refunds.